Design, Synthesis, and Development of Novel Intracellular Allosteric Modulators of CXC Chemokine Receptor 1 and 2 - Francis, Rhys (2024)
Chemokine receptors, CXC chemokine receptor 1 (CXCR1) and CXC chemokine receptor 2 (CXCR2) play pivotal roles in various neutrophil-mediated inflammatory diseases, including COPD, asthma, and psoriasis. Additionally, evidence is mounting for the involvement of neutrophils and the CXCL8-CXCR1/2 axis in the progression and metastasis in multiple cancers. Their role in multiple disease states has made them an appealing candidate for therapeutic intervention for over a decade.